GOOD CORPORATE GOVERNANCE DALAM PERSPEKTIF KONVENSIONAL DAN ISLAM - yani suryani; desi ika (VALUE, 2022)
The purpose of writing this article is to provide an overview/explanation related to Good Corporate Governance in both conventional and Islamic views. The writing of this article uses the method of literature study or literature study. The stages carried out in analyzing conventional Good Corporate Governance/GCG and Good Corporate Governance in an Islamic view are to collect literature or studies and scientific works that discuss conventional Good Corporate Governance and GCG in an Islamic view. The next step is to identify the problem under study, then classify the problem and make a presentation that discusses the topic under study and then draws a conclusion. The results of Good Corporate Governance (GCG) in terms of conventional and Islamic concepts basically have similarities, the difference is the existence of sharia compliance (sharia compliance) or the application of sharia principles in the operations of Islamic banks and the existence of DPS (Sharia Supervisory Board) which has the task of implementing supervisory function in sharia banking as well as the existence of DSN-MUI (National Sharia Council of the Indonesian Ulema Council).